Practicing democracy : elections and political culture in Imperial Germany - Anderson, Margaret Lavinia (Princeton paperbacks., 2000)
What happens when manhood suffrage, a radically egalitarian institution, gets introduced into a deeply hierarchical society? In her sweeping history of Imperial Germany's electoral culture, Anderson shows how the sudden opportunity to "practice" democracy in 1867 opened up a free space in the land of Kaisers, generals, and Junkers. Originally designed to make voters susceptible to manipulation by the authorities, the suffrage's unintended consequence was to enmesh its participants in ever more democratic procedures and practices. The result was the growth of an increasingly democratic culture in the decades before 1914. Explicit comparisons with Britain, France, and America give us a vivid picture of the coercive pressures--from employers, clergy, and communities--that German voters faced, but also of the legalistic culture that shielded them from the fraud, bribery, and violence so characteristic of other early "franchise regimes." We emerge with a new sense that Germans were in no way less modern in the practice of democratic politics. Anderson, in fact, argues convincingly against the widely accepted notion that it was pre-war Germany's lack of democratic values and experience that ultimately led to Weimar's failure and the Third Reich. Practicing Democracy is a surprising reinterpretation of nineteenth- and early twentieth-century Germany and will engage historians concerned with the question of Germany's "special path" to modernity sociologists interested in obedience, popular mobilization, and civil society political scientists debating the relative role of institutions versus culture in the transition to democracy. By showing how political activity shaped and was shaped by the experiences of ordinary men and women, it conveys the excitement of democratic politics.